Malaysia Economic Monitor, June 2015 : Transforming Urban Transport - World Bank (Washington, DC, 2015)
After a strong finish in 2014, growth moderated in early 2015. Malaysia’s economy expanded by 6.0 percent in 2014, accelerating to 7.3 percent q/q saar in Q42014 due to resilient domestic demand and a pick-up of exports. Growth moderated to 4.7 percent q/q saar in Q1 2015 on account of weaker external demand, but domestic demand remained strong. To transform the planning and delivery of urban transport, Malaysia may consider prioritizing the following reforms: (a) Establish lead transport agencies at the conurbation level that spearhead an integrated approach towards the planning and delivery of urban transport across different modes; (b) identify and implement sustainable financing mechanisms for the lead agency. Introducing local taxes on fuel would not only result in environmental gains and trim the fiscal deficit (by RM10-19 billion), but also fund transport (for example, 24 percent of Vancouver’s transit system is funded by municipal gas taxes). Reviewing impediments to transit-oriented development will be another option, but should be considered alongside implications for affordability and inclusion; and (c) align policies to promote public transport with incentives to discourage the usage of private transport in congested areas. Introducing congestion pricing in areas well-covered by public transport as is done inSingapore will be an example of such policies.